99mTc-polyphosphonate labelling: enhancement of a novel method for the quantification of osteogenic differentiation of MSCs in vitro - Großner, Tobias; Helbig, Lars; Schmidmaier, Gerhard; Haberkorn, Uwe; Gotterbarm, Tobias (Injury, 2022)
Bone tissue engineering is a fast-growing field in regenerative medicine. Consequently, there is a high demand for new, fast and reliable methods to track and quantify the osteogenic differentiation of cells. Recently, a novel method was published to non-destructively quantify the hydroxyapatite content of monolayer and 3-dimensional mesenchymal stem cell cultures using the ability of 99mTechnetium-methylene diphosphonate (MDP), a well-established tracer in clinical nuclear medicine, to bind to newly synthesized hydroxyapatite. In the present study, two other commonly used 99mTechnetium tracers, 2,3-dicarboxypropane-1,1-diphosphonate (DPD) and hydroxydiphosphonate (HDP), were evaluated to see if they could also be used for the same purpose. Furthermore, we investigated if labelling at various timepoints influenced the effectiveness of the labelling. The results were analysed using one-factor ANOVA followed by Bonferroni post-hoc testing. This revealed a highly significant difference between the three osteogenic groups at each timepoint compared to their corresponding negative controls. However, there was no statistically significant difference between the three different tracers (MDP, DPD, HDP) in the osteogenic groups. Therefore all three tracers are of similar value when quantifying the extracellular hydroxylapatite content in osteogenic stem cells cultures.
99m im Titel ist hochgestellt
Gesehen am 04.01.2023